Elevated Bile Acids Induce Circadian Rhythm Sleep Disorders in Chronic Liver DiseasesSummary - Lan Zhou; Min Yan; Qin Luo; Wen Qiu; Yu-Ru Guo; Xiao-Qing Guo; Hong-Bin Yu; Jing-Ru Huo; Yan-Lin Feng; De-Ping Wang; Teng Sun; Kai-Fang Wang; et al. (Cellular and Molecular Gastroenterology and Hepatology)
Background & Aims: Sleep disorders (SDs) are common in chronic liver diseases (CLDs). Some SDs arise from impaired internal clock and are, hence, circadian rhythm SDs (CRSDs). Bile acids (BAs), whose levels are increased in many CLDs, reciprocally interact with circadian rhythm. This study explores the mechanisms underlying CRSDs in CLDs and novel therapies. Methods: We monitored the sleep of patients with CLD using actigraphic watch and established male mouse cholemia models by feeding with BA or bile duct ligation. Sleep-wake cycle and circadian rhythm were analyzed by electroencephalogram-electromyography and locomotor wheel-running experiments. Results: Patients with CLD showed CRSD-like phenotypes including increased night activity and early awakening, which were strongly correlated with increased BA levels (ie, cholemia). CRSDs, including shortened circadian period, were recapitulated in 2 cholemic mouse models. Mechanistically, elevated BAs in the suprachiasmatic nucleus (SCN) activated BA receptor Takeda G protein-coupled receptor 5 (Tgr5), which, in turn, increased the level and phosphorylation of Period2 (Per2), a master rhythm regulator, through extracellular signal-regulated kinase (Erk) and casein kinase 1ε (CK1ε). Per2 phosphorylation inhibited its nuclear import, which would release its transcriptional inhibition and expedite the circadian cycle. Cholemia also blunted the light entrainment response and light-induced phase change of SCN mediated by the neurons expressing gastrin releasing peptide through Tgr5-Per2 axis. BA sequestrant or CK1 inhibitor reversed the CRSDs in cholemic mice by restoring Per2 distribution. Conclusions: Cholemia is a major risk factor for CRSDs in CLDs and, hence, a promising target in future clinical study.